Screening and prophylaxis of retinal degenerations prior to refractive surgery - Venkatesh, Ramesh (Indian J Ophthalmol, 2020)
The need and demand for surgical correction of refractive errors, particularly myopia, has been increasing. Degenerations involving the peripheral retina are common in myopes and can result in a rhegmatogenous retinal detachment. There are no clear guidelines for retinal screening and management of asymptomatic retinal degenerations prior to refractive surgery or for follow-up of these patients. This article aims to provide a set of guidelines for the management of retinal degenerations in eyes undergoing refractive surgeries.